Aluminum-based hydrophobic material for aircraft fuselage material and preparation method of aluminum-based hydrophobic material
By preparing aluminum-based hydrophobic materials on the surface of the aircraft fuselage, and using composite coatings of graphene and hydrophobic vapor-phase nanosilicon dioxide, electric/photothermal coupling is achieved, the problem of deicing the aircraft fuselage is solved, reducing energy consumption and improving deicing efficiency.
Patent Information
- Application Number
- CN202510480338.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-07-25
AI Technical Summary
The prior art is difficult to effectively achieve all-weather prevention of deicing on the surface of the aircraft fuselage, and it consumes a high energy consumption.
Using composite coating technology, aluminum-based hydrophobic materials are prepared, combined with graphene and hydrophobic vapor-phase nanosilicon dioxide to form an electrothermal/photothermal coupled hydrophobic coating, and use light and electric heat effects to achieve rapid deicing.
Realize efficient deicing at low voltages, reduce energy consumption, enhance passive deicing effect, and improve the flight safety and quality of the aircraft.
Smart Images

Figure CN120365814A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of aircraft fuselage anti-icing materials, and in particular relates to an aluminum-based hydrophobic material for aircraft fuselage materials and a preparation method thereof. Background Art
[0002] Icing is a common phenomenon in our daily life, which brings many inconveniences to our daily life. For aircraft that often operate in high-altitude environments, icing can pose a huge threat to flight safety. In order to ensure the smooth flight of aircraft and reduce the energy consumption of aircraft, various research institutions are actively developing various efficient anti-icing materials.
[0003] Among many anti-icing materials, the composite coating method has attracted much attention due to its simplicity, high efficiency, and multi-functionality. The arrangement structure of the composite coating largely determines its application properties. The function of each coating is mainly realized by the properties of the "action factors" attached thereto. Among them, graphene (GR), as a material with good thermal conductivity and electrical conductivity, is widely used in photothermal coatings, and hydrophobicity is mainly achieved by low surface energy modification and rough structure. Therefore, a (PDMS-SiO2) solution is selected as the coating material for the outermost layer, combined with a copper mesh electrothermal element on the back of the aluminum sheet, to form an electrothermal / photothermal coupled hydrophobic coating.
[0004] For example, Chinese Patent: CN113549966A discloses "a superhydrophobic coating for anti-icing on a metal surface and a preparation method thereof". First, an insoluble electrode plate is used as the anode and a metal plate is used as the cathode, and a Zn-Ni alloy coating is electroplated on the cathode by a constant temperature and constant pressure electroplating technique; aluminum nitrate and sodium carbonate are dissolved in deionized water to obtain a hydrothermal reaction solvent, and then the prepared Zn-Ni alloy coating is placed in the hydrothermal reaction solvent to obtain a metal surface Zn-Al layered double metal hydroxide; finally, the sample obtained by the hydrothermal reaction is soaked and modified with a low surface energy modifier to obtain an anti-icing superhydrophobic coating. The superhydrophobic coating prepared by the present invention has excellent non-wettability and anti-icing performance.
[0005] The developed (PDMS-SiO2 / Paint / GR@etching Al) composite hydrophobic coating can achieve all-weather de-icing by using photo-electrothermal coupling, has a certain anti-icing effect, and the stability of the coating is good. This method improves the efficiency of the anti-icing work of the aircraft fuselage, reduces the energy consumption during the flight of the aircraft, and improves the flight quality and safety factor of the aircraft. Summary of the Invention
[0006] In view of this, the present invention aims to overcome the defects in the prior art and proposes an aluminum-based hydrophobic material for aircraft fuselage materials and a preparation method thereof. The (PDMS-SiO2 / Paint / GR@etching Al) aluminum-based hydrophobic material prepared by the composite coating technology can not only de-ice quickly and effectively when powered on, but also reduce or alleviate the surface icing phenomenon by using the refraction and absorption of light when light is present.
[0007] To achieve the above object, the technical solution of the present invention is realized as follows:
[0008] A preparation method of an aluminum-based hydrophobic material for aircraft fuselage materials, comprising the following steps:
[0009] (1) Immerse the aluminum sheet in a 1 mol / L hydrochloric acid standard solution according to a solid-liquid ratio of 1:30 for reaction, then take out the aluminum sheet, rinse it with deionized water, and put it in an oven to dry to obtain a base aluminum sheet sample;
[0010] (2) Prepare a base solution by mixing epoxy resin and curing agent in a ratio of 4:1, then add graphene to it, and obtain an EP-GR solution after magnetic stirring and ultrasonic treatment. Spray the EP-GR solution on the base aluminum sheet to obtain a GR@etching Al sample;
[0011] (3) At a distance of 20 mm from the aluminum sheet, evenly spray black metal paint on the surface of the GR@etching Al sample to obtain a Paint / GR@etching Al sample;
[0012] (4) Prepare a PDMS solution, add hydrophobic fumed nano-silica to it, and obtain a PDMS-SiO2 solution after ultrasonic treatment. Spray the PDMS-SiO2 on the surface of the Paint / GR@etching Al sample, and obtain a PDMS-SiO2 / Paint / GR@etching Al sample after curing and drying. The photothermal materials used in this finished product are graphene (GR) and black metal paint (Paint), and the hydrophobic materials are polydimethylsiloxane (PDMS) and hydrophobic fumed nano-silica (SiO2).
[0013] Furthermore, the specifications of the aluminum sheet in step (1) are: a square with a length of 50 mm, a width of 50 mm, and a thickness of 0.2 mm; the concentration of the hydrochloric acid standard solution is 1-10 mol / L; the reaction time is 1-10 h; the drying temperature is 50-60 °C, and the drying time is 5-10 min.
[0014] Furthermore, the mass concentration of EP in the EP-GR solution in step (2) is 10-50%, and the mass concentration of the curing agent is 1-20%.
[0015] Further, in the EP-GR solution in step (2), the mass concentration of graphene is 0.2-20%, the temperature of magnetic stirring is 15-25°C, the stirring time is 30-120 min, and the ultrasonic stirring time is 30-120 min.
[0016] Further, the spraying process of the ferrous metal paint in step (3) is specifically as follows: After spraying for 10 s each time, the substrate aluminum sheet is left standing for 1 min. After repeating three times, it is placed in an oven and dried at 80°C for 1 h.
[0017] Further, in the PDMS-SiO2 solution in step (4), the mass concentration of the PDMS solution is 1-20%, the mass concentration of the curing agent is 0.1-10%, and the mass concentration of n-hexane is 1-92.3%.
[0018] Further, in the PDMS-SiO2 solution in step (4), the mass concentration of nano-SiO2 is 0.1-20%, and the ultrasonic time is 30-120 min; after spraying the PDMS-SiO2 solution, the PDMS-SiO2 / Paint / GR@etching Al sample is placed in an oven at 100°C for curing and drying for 4 h.
[0019] An aluminum-based hydrophobic material for aircraft fuselage materials prepared by using the above preparation method.
[0020] An application of an aluminum-based hydrophobic material for aircraft fuselage materials, and the application of the aluminum-based hydrophobic material in the field of aircraft fuselage anti-icing and de-icing materials.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] The aluminum-based hydrophobic material for aircraft fuselage materials described in the present invention selects 1060 aluminum as the original aluminum sheet, which has the characteristics of light weight and high strength, and at the same time has good electrical and thermal conductivity and excellent corrosion resistance, making it an ideal aircraft fuselage material. The selected graphene (GR) powder can significantly improve its photothermal performance and enhance the passive de-icing effect. The selected epoxy resin (EP) has good adhesion performance, which can make the graphene powder particles better adhere to the metal substrate, and it has excellent mechanical properties, which enhances the strength of the coating to a certain extent. The selected (PDMS) has excellent hydrophobic performance, which can enhance the non-wettability of the coating surface. The selected gas-phase hydrophobic nano-silica (SiO2) increases the surface roughness, and it itself also has certain hydrophobicity, which can cooperate with (PDMS) to improve the surface hydrophobicity. The copper mesh loaded on the back has good electrothermal performance, and a relatively low voltage can make the surface of the sample reach a relatively high equilibrium temperature, greatly reducing its active de-icing energy consumption.
[0023] The aluminum-based hydrophobic material (PDMS-SiO2 / Paint / GR@etching Al) described in the present invention has good electrothermal performance and can cooperate with photothermal performance and superhydrophobicity to become an ideal anti-icing material for metal substrates. When the voltage is 1.5V, the surface equilibrium temperature reaches 74.6°C, and it can melt ice particles within 164s and melt a 3-mm-thick ice layer within 360s. This material also has photothermal performance. Under one light intensity, the photothermal effect can reach an equilibrium temperature of 46.3°C. The coating of this material shows good hydrophobicity, with a water contact angle reaching 137.4°, and effectively delays the freezing time of droplets to 360s at an ambient temperature of -10°C. In addition, this multi-functional anti-icing coating based on aluminum sheets has relatively excellent stability and self-cleaning ability. Description of the Drawings
[0024] Figure 1 SEM diagrams of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention;
[0025] Figure 2 EDS diagram of Example 1 of the present invention;
[0026] Figure 3 Schematic diagram of the delayed icing effect of Example 1 of the present invention;
[0027] Figure 4 Schematic diagram of the equilibrium temperature of Example 1 of the present invention under different voltages;
[0028] Figure 5 Schematic diagram of the electrothermal cycle stability of Example 1 of the present invention at 1.5V voltage;
[0029] Figure 6 Schematic diagram of the electrothermal anti-icing effect of Example 1 and Comparative Example 1 of the present invention;
[0030] Figure 7 Schematic diagram of the equilibrium temperature of Example 1 of the present invention under different light intensities;
[0031] Figure 8 Schematic diagram of the photothermal cycle stability of Example 1 of the present invention at 1.5 light intensities;
[0032] Figure 9 Schematic diagram of the photothermal anti-icing effect of Example 1 and Comparative Example 1 of the present invention;
[0033] Figure 10 Schematic diagram of the self-cleaning ability of Example 1 and Comparative Example 1 of the present invention. Detailed Embodiments
[0034] Unless otherwise defined, the technical terms used in the following examples have the same meanings as commonly understood by those skilled in the art to which the present invention pertains. The test reagents used in the following examples are all conventional biochemical reagents unless otherwise specified; the experimental methods are all conventional methods unless otherwise specified.
[0035] The letter abbreviations mentioned in the present invention are all fixed abbreviations in the art, and the explanations of some of the letters are as follows: Etching Al: substrate aluminum sheet; Paint: black metal paint; GR: graphene; EP: epoxy resin; PDMS: polydimethylsiloxane; SiO2: silicon dioxide; SEM: scanning electron microscope; EDS: energy dispersive spectrometer.
[0036] The present invention will be described in detail below with reference to the examples.
[0037] Example 1
[0038] This embodiment prepares an aluminum-based hydrophobic material with a dual energy conversion mechanism for aircraft fuselage materials according to the following steps;
[0039] First step, prepare a sample of substrate aluminum sheet (Etching Al)
[0040] Put a square original aluminum sheet with a length and width of 50 mm and a thickness of 0.2 mm into a beaker containing 1 mol / L hydrochloric acid standard solution, let it react for 1 h, then take out the aluminum sheet, rinse it with deionized water and put it into an oven for drying. The temperature of the drying oven is 50 - 60 °C, and the drying time is 5 - 10 min, to obtain a sample of substrate aluminum sheet (Etching Al).
[0041] Second step, prepare a sample of (GR@etching Al)
[0042] Add a certain mass of T-31 type curing agent (2%) to (EP) (5%), then add a certain mass of graphene powder (0.1%) to it, stir on a magnetic stirrer for 30 min, the stirring temperature is 15 - 25 °C, and then perform ultrasonic treatment for 30 min to prepare an (EP-GR) solution. Spray this solution on the substrate aluminum sheet and put it into an oven for curing and drying to obtain a sample of (GR@etchingAl).
[0043] Third step, prepare a sample of (Paint / GR@etching Al)
[0044] Spray black metal paint on the surface of the (GR@etching Al) sample. During the spraying process, let the substrate aluminum sheet stand for 1 min every 10 s of spraying. After repeating three times, put it into an oven and dry at 80 °C for 1 h to obtain a sample of (Paint / GR@etching Al).
[0045] Step 4: Prepare the (PDMS) solution
[0046] Add a certain mass of (PDMS) (4%) to a reagent bottle filled with n-hexane, then add a certain mass of curing agent and place it on a magnetic stirrer. The stirring temperature is 15 - 25°C and the stirring time is 30 min to obtain the (PDMS) solution.
[0047] Step 5: Prepare the (PDMS-SiO2) solution
[0048] Add a certain amount of hydrophobic fumed silica powder (SiO2) (0.2%) to the prepared (PDMS) solution, and then perform ultrasonic treatment for 30 min to obtain the (PDMS-SiO2) solution.
[0049] Step 6: Prepare the (PDMS-SiO2 / Paint / GR@etching Al) sample
[0050] Spray the (PDMS-SiO2) solution onto the prepared (Paint / GR@etching Al) sample, place it in an oven at 100°C for curing and drying for 4 h, and obtain the (PDMS-SiO2 / Paint / GR@etching Al) sample after drying and curing.
[0051] Comparative Example 1
[0052] In this embodiment, an (Etching Al) aluminum sheet for aircraft fuselage anti-icing material is prepared according to the following steps;
[0053] Put a square original aluminum sheet with a length and width of 50 mm and a thickness of 0.2 mm into a beaker containing 1 mol / L hydrochloric acid standard solution, let it react for 1 h, then take out the aluminum sheet, rinse it with deionized water and put it into an oven for drying. The temperature of the drying oven is 50 - 60°C and the drying time is 5 - 10 min to obtain the substrate aluminum sheet (Etching Al).
[0054] Comparative Example 2
[0055] In this embodiment, a (GR@etching Al) aluminum sheet for aircraft fuselage anti-icing material is prepared according to the following steps;
[0056] Step 1: Prepare the (EP-GR) solution. Add a certain mass of curing agent to the (EP) solution, then add a certain mass of graphene powder, stir on a magnetic stirrer for 30 min, the stirring temperature is 15 - 25°C, and then perform ultrasonic treatment for 30 min to obtain the (EP-GR) solution. Spray this solution onto the substrate aluminum sheet and place it in an oven for curing and drying. Obtain the (GR@etching Al) sample.
[0057] Step 2: Prepare (GR@etching Al).
[0058] Spray this solution onto the substrate aluminum sheet (Etching Al), and place it in an oven for curing and drying to obtain the (GR@etching Al) sample.
[0059] Comparative Example 3
[0060] In this embodiment, a (Paint / GR@etching Al) aluminum sheet for aircraft fuselage anti-icing material is prepared according to the following steps;
[0061] Step 1: Spray black metallic paint on the surface of the GR@etching Al sample. During the spraying process, after spraying for 10 s each time, let the substrate aluminum sheet stand for 1 min, and repeat three times.
[0062] Step 2: Prepare the (Paint / GR@etching Al) aluminum sheet.
[0063] After the spraying is completed, place it in an oven and dry it at 80 °C for 1 h to obtain the (Paint / GR@etching Al) sample.
[0064] Refer to Figure 1 , Figure 1 For the SEM images of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, as shown in the figure, (Etching Al) shows a snowflake-like pore structure on the surface due to chemical etching with hydrochloric acid, proving the successful construction of the rough structure; the surface of (GR@etching Al) forms a protrusion structure due to the spraying of graphene and the partial aggregation of graphene; the surface of (Paint / GR@etching Al) is relatively smooth due to the wrapping of the sprayed black metallic paint; the surface roughness of (PDMS-SiO2 / Paint / GR@etching Al) increases to a certain extent due to low surface energy modification.
[0065] Refer to Figure 2 , Figure 2 For the EDS image of Example 1, as shown in the figure, four element distributions are mainly presented on the surface of the final sample. The extensive distribution of Si element proves the successful introduction of silica.
[0066] Refer to Figure 3 , Figure 3 For the schematic diagram of the delayed icing effect of Example 1, as shown in the figure, through the construction of a series of photothermal and hydrophobic layers, the icing time of the final sample is extended from the initial 18 s to 360 s.
[0067] Refer to Figure 4 , Figure 4Schematic diagram of the equilibrium temperature of Example 1 at different voltages. As shown in the figure, with the gradual increase of the voltage, the equilibrium temperature on the surface of the sample also increases. When the applied voltage is only 1.8 V, the equilibrium temperature on the surface can reach about 80 °C.
[0068] See Figure 5 , Figure 5 Schematic diagram of the electrothermal cycle stability of Example 1 at a voltage of 1.5 V. As shown in the figure, the sample (PDMS-SiO2 / Paint / GR@etching Al) can reach the equilibrium temperature within about 120 s in each cycle, and then quickly return to the initial temperature within 60 s, which to a certain extent proves the stability of its electrothermal performance.
[0069] See Figure 6 , Figure 6 Schematic diagram of the electrothermal de-icing effect of Example 1 and Comparative Example 1. As shown in the figure, compared with (Etching Al), the de-icing effect of the sample (PDMS-SiO2 / Paint / GR@etching Al) on ice particles and ice layers is significantly better than that of Etching Al.
[0070] See Figure 7 , Figure 7 Schematic diagram of the equilibrium temperature of Example 1 under different light intensities. As shown in the figure, with the increase of the light intensity, the surface equilibrium temperature also increases. At a light intensity of 1.8, the surface equilibrium temperature of the sample (PDMS-SiO2 / Paint / GR@etching Al) can reach about 48 °C.
[0071] See Figure 8 , Figure 8 Schematic diagram of the photothermal cycle stability of Example 1 at a light intensity of 1.5. As shown in the figure, the sample (PDMS-SiO2 / Paint / GR@etching Al) can reach the equilibrium temperature within about 180 s in each cycle, and then return to the initial temperature within 120 s, which to a certain extent proves the stability of its photothermal performance.
[0072] See Figure 9 , Figure 9 Schematic diagram of the photothermal de-icing effect of Example 1 and Comparative Example 1. As shown in the figure, compared with (Etching Al), the de-icing effect of the sample (PDMS-SiO2 / Paint / GR@etching Al) on ice particles and ice layers is significantly better than that of (Etching Al).
[0073] See Figure 10 , Figure 10Schematic diagram of the self-cleaning ability of Example 1 and Comparative Example 1. As shown in the figure, after the surface of the sample (PDMS-SiO2 / Paint / GR@etching Al) was contaminated, it was rinsed with deionized water, and the surface contaminants were carried away by the water and thus slipped off, and the surface remained clean as a whole.
[0074] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A preparation method of an aluminum-based hydrophobic material for aircraft fuselage materials, characterized in that: It includes the following steps: (1) Immerse the aluminum sheet in a 1 mol / L hydrochloric acid standard solution according to a solid-liquid ratio of 1:30 for reaction. Then take out the aluminum sheet, rinse it with deionized water, and place it in an oven for drying to obtain a substrate aluminum sheet sample; (2) Prepare a substrate solution by mixing epoxy resin and curing agent at a ratio of 4:
1. Then add graphene to it. After magnetic stirring and ultrasonic treatment, an EP-GR solution is obtained. Spray it on the substrate aluminum sheet to obtain a GR@etching Al sample; (3) At a distance of 20 mm from the aluminum sheet, evenly spray black metal paint on the surface of the GR@etching Al sample to obtain a Paint / GR@etching Al sample; (4) Prepare a PDMS solution, add hydrophobic fumed nano-silica to it. After ultrasonic treatment, a PDMS-SiO2 solution is obtained. Spray the PDMS-SiO2 on the surface of the Paint / GR@etching Al sample. After curing and drying, a PDMS-SiO2 / Paint / GR@etching Al sample is obtained.
2. The preparation method of the aluminum-based hydrophobic material for aircraft fuselage materials according to claim 1, characterized in that: The specifications of the aluminum sheet in step (1) are: a square with a length of 50 mm, a width of 50 mm, and a thickness of 0.2 mm; the concentration of the hydrochloric acid standard solution is 1-10 mol / L; the reaction time is 1-10 h; the drying temperature is 50-60 °C, and the drying time is 5-10 min.
3. The preparation method of the aluminum-based hydrophobic material for aircraft fuselage materials according to claim 1, characterized in that: In the EP-GR solution in step (2), the mass concentration of EP is 10-50%, and the mass concentration of the curing agent is 1-20%.
4. The preparation method of the aluminum-based hydrophobic material for aircraft fuselage materials according to claim 1, characterized in that: In the EP-GR solution in step (2), the mass concentration of graphene is 0.2-20%, the temperature of magnetic stirring is 15-25 °C, the magnetic stirring time is 30-120 min, and the ultrasonic time is 30-120 min.
5. The preparation method of the aluminum-based hydrophobic material for aircraft fuselage materials according to claim 1, characterized in that: The specific process of spraying the black metal paint in step (3) is: after spraying for 10 s each time, let the substrate aluminum sheet stand for 1 min. Repeat three times and then put it into an oven and dry it at 80 °C for 1 h.
6. The preparation method of the aluminum-based hydrophobic material for aircraft fuselage materials according to claim 1, characterized in that: In the PDMS-SiO2 solution in step (4), the mass concentration of the PDMS solution is 1-20%, the mass concentration of the curing agent is 0.1-10%, and the mass concentration of n-hexane is 1-92.3%.
7. The preparation method of the aluminum-based hydrophobic material for aircraft fuselage materials according to claim 1, characterized in that: In the PDMS-SiO2 solution in step (4), the mass concentration of nano-SiO2 is 0.1-20%, and the ultrasonic time is 30-120 min; after spraying the PDMS-SiO2 solution, put the PDMS-SiO2 / Paint / GR@etching Al sample into an oven at 100 °C for curing and drying for 4 h.
8. An aluminum-based hydrophobic material for aircraft fuselage materials prepared by using the preparation method described in any one of claims 1-7.
9. Use of the aluminum-based hydrophobic material for aircraft fuselage materials according to claim 8, characterized in that: The application of the aluminum-based hydrophobic material in the field of aircraft fuselage anti-icing and de-icing materials.
Citation Information
Patent Citations
Anti-icing super-hydrophobic coating on metal surface and preparation method of anti-icing super-hydrophobic coating
CN113549966A